GSC: a real-time communication scheme for IEEE 802.11e industrial systems - Raimundo Viegas Júnior (2007)
This paper proposes a new real-time communication scheme for IEEE 802.11e HCCA networks. The proposed communication scheme is called Group Sequential Communication (GSC) and it aims the reduction of the polling overhead associated to the real-time message transmission when using the HCCA function. The GSC scheme partially eliminates the polling inefficiency, by means of a virtual token passing procedure among polled stations. Thus, it reduces the number of exchanged messages between the HCCA controller and the polled stations. The GSC uses a real-time group concept, where the real-time members of the group are granted a sequential access to the communication medium.